Direct Electrolytic Splitting of Seawater: Activity, Selectivity, Degradation, and Recovery Studied from the Molecular Catalyst Structure to the Electrolyzer Cell Level. Issue 22 (23rd May 2018) - Dresp, Sören; Dionigi, Fabio; Loos, Stefan; Ferreira de Araujo, Jorge; Spöri, Camillo; Gliech, Manuel; Dau, Holger; Strasser, Peter
Abstract: Seawater electrolysis faces fundamental chemical challenges, such as the suppression of highly detrimental halogen chemistries, which has to be ensured by selective catalyst and suitable operating conditions. In the present study, nanostructured NiFe‐layered double hydroxide and Pt nanoparticles are selected as catalysts for the anode and cathode, respectively. The seawater electrolyzer is tested successfully for 100 h at maximum current densities of 200 mA cm −2 at 1.6 V employing surrogate sea water and compared to fresh water feeds. Different membrane studies are carried out to reveal the cause of the current density drop. During long‐term dynamic tests, under simulated day‐night cycles, an unusual cell power performance recovery effect is uncovered, which is subsequently harnessed in a long‐term diurnal day‐night cycle test. The natural day‐night cycles of the electrolyzer input power can be conceived as a reversible catalyst materials recovery treatment of the device when using photovoltaic electricity sources. To understand the origin of this reversible recovery on a molecular materials level, in situ extended X‐ray absorption fine structure and X‐ray near‐edge region spectra are applied. Abstract : For the first time, a working alkaline sea water electrolyzer, designed for splitting chloride‐containing seawater directly and selectively into hydrogen and oxygen, is analyzed from the molecular materials chemistry level, to the electrochemical single cell performance, to membrane and cell degradation patterns, all the way to cell‐level power performance recovery effects.